Donor/recipient origin of lung cancer after lung transplantation by DNA short tandem repeat analysis - De Wolf, Julien; Robin, Edouard; Vallee, Alexandre; Cohen, Justine; Hamid, Abdul; Roux, Antoine; Leguen, Morgan; Beaurepere, Romane; Bieche, Ivan; Masliah-Planchon, Julien; Glorion, Matthieu; Allory, Yves; et al. (Frontiers in Oncology, 2023)
Lung cancer is more common in post-transplanted recipients than in the general population. The objective of this study was to examine the chimerism donor/recipient cell origin of graft cancer in recipients of lung transplant.A retrospective chart review was conducted in the Foch hospital for all lung transplantation from 1989 to 2020. Short tandem repeat PCR (STR-PCR) analysis, the gold standard technique for chimerism quantification, was used to determine the donor/recipient cell origin of lung cancers of transplanted patients.Fourteen (1.4%) of the 1,026 transplanted patients were found to have a graft lung cancer after lung transplant, one developed 2 different lung tumors in the same lobe. Among the 15 lung tumors, in 10 (67%) patients presented adenocarcinoma, four (27%) squamous cell carcinoma and one small cell lung cancer. The STR analysis showed that the origin of the cancer was the donor in 10 patients (71%), the recipient in three patients (21%) and was undetermined for one patient. The median time to diagnosis was 62 months.The prevalence of lung cancer in lung transplant recipients is very low. However, the results of our study showed the heterogeneity of genetic alterations with 21% of recipient origin. Our result highlights the importance of donor selection but also medical supervision after lung transplantation.